Effects of improvements in non-motorised transport facilities on active mobility demand in a residential township. (March 2020) - Zhou, Q.; Che, M.; Koh, P.P.; Wong, Y.D.
Abstract: Introduction: Sustainable and eco-friendly mobility is of great significance to alleviate urbanisation pressure and to improve urban quality of life. Providing good non-motorised transport (NMT) facilities for active mobility (covering principally walking and cycling) is an effective way to promote bicycle use which in turn improves one's physical health. Singapore, with a tight space constraint, has been focusing strongly on active mobility developments over the recent decade which can depress motorisation growth and thereby alleviate road traffic congestion. Methods: In order to evaluate the effects of upgrading a cycling infrastructural network on active mobility in a residential township in Singapore, a before-and-after study was applied to evaluate NMT infrastructure developments. Three rounds of perception surveys and traffic count surveys were conducted before and after the upgrading of the cycling network. The number of cyclists and pedestrians was enumerated and spatial distributions of cyclists and pedestrians in AMK town are presented using Geographic Information System (GIS). Results: Traffic count surveys show that the numbers of cyclists and pedestrians have increased on a large proportion of the investigated pathway segments after upgrading the cycling network. Paired two-tailed t-test results suggest significant differences at 95% confidence level between the before-and-after counts after the cycling network was implemented in 2017. Perception surveys show that a higher proportion of pedestrians and cyclists/PMD riders feel safe to share the footpath, feel safe and convenient to cycle, as well as feel satisfied with current cycling infrastructure, as compared to 2016. Conclusions: The enhanced cycling network not only attracts more cyclists and encourages cycling activities, but it also increases walking activities, and has positive impact on the mobility of both cyclists and pedestrians. As the city grows in population and housing density, the health benefits of the cycling network are more than a change in active mobility usage, but a whole community transformation. Highlights: The implementation of cycling network in a residential township in Singapore is evaluated. Before-and-after study is applied to examine the impacts of non-motorised transport (NMT) activities on cycling network. On-site surveys were conducted to evaluate the usage of NMT on cycling network. Notable increase in NMT activities was observed after the implementation of cycling network.